2019
DOI: 10.1002/jbmr.3742
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte Death and Bone Overgrowth in Mice Lacking Fibroblast Growth Factor Receptors 1 and 2 in Mature Osteoblasts and Osteocytes

Abstract: Fibroblast growth factor (FGF) signaling pathways have well‐established roles in skeletal development, with essential functions in both chondrogenesis and osteogenesis. In mice, previous conditional knockout studies suggested distinct roles for FGF receptor 1 (FGFR1) signaling at different stages of osteogenesis and a role for FGFR2 in osteoblast maturation. However, the potential for redundancy among FGFRs and the mechanisms and consequences of stage‐specific osteoblast lineage regulation were not addressed. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 87 publications
(186 reference statements)
1
33
0
Order By: Relevance
“…185 FGFR1 signaling in mature osteoblasts/osteocytes is required for the survival of osteocytes and bone mass maintaining in mice. 186 In addition, our group revealed that FGFR1 can positively regulate the differentiation and resorption activity of osteoclasts. 187 GOF mutation in FGFR2 (S252W) resulted in increased apoptosis of osteogenic cells, 188 disturbed osteoblastic proliferation and differentiation, and the presence of ectopic cartilage at the midline sagittal suture.…”
Section: Fgf/fgfr Signaling In Skeleton Development and Homeostasismentioning
confidence: 93%
See 1 more Smart Citation
“…185 FGFR1 signaling in mature osteoblasts/osteocytes is required for the survival of osteocytes and bone mass maintaining in mice. 186 In addition, our group revealed that FGFR1 can positively regulate the differentiation and resorption activity of osteoclasts. 187 GOF mutation in FGFR2 (S252W) resulted in increased apoptosis of osteogenic cells, 188 disturbed osteoblastic proliferation and differentiation, and the presence of ectopic cartilage at the midline sagittal suture.…”
Section: Fgf/fgfr Signaling In Skeleton Development and Homeostasismentioning
confidence: 93%
“… 185 FGFR1 signaling in mature osteoblasts/osteocytes is required for the survival of osteocytes and bone mass maintaining in mice. 186 In addition, our group revealed that FGFR1 can positively regulate the differentiation and resorption activity of osteoclasts. 187 …”
Section: Fgf Signaling In Skeleton Development and Repair/regeneratiomentioning
confidence: 93%
“…Osteoblasts lining the trabecular bone were identified from the H & E stained femur sections, number of cells were expressed in terms of the bone surface. H & E stained sections were also used for enumerating alive, dying, and dead osteocytes in the cortical bones using a previously published method 14 . For osteoclast detection in femurs, Tartrate‐resistant acid phosphatase (TRAP) staining was performed using TRAP/ALP Stain Kit according to manufacturer's instructions (#294‐67001, Wako Chemicals, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Similar findings were observed after conditional inactivation of Fgfr1 and Fgfr2 in osteocytes. These data suggest that FGFR1 and/or FGFR2 expression in mature osteoblasts/osteocytes is required for osteocyte survival and regulation of bone mass during postnatal bone growth (McKenzie et al 2019). A previous report indicated that conditional knockout of Fgfr1 in osteocytes in mice results in decreased osteocyte-specific gene expression but no overt skeletal phenotype (Xiao et al 2014).…”
Section: R259mentioning
confidence: 65%